Data fusion based on Searchlight analysis for the prediction of Alzheimer's disease. (15th December 2021) - Arco, Juan E.; Ramírez, Javier; Górriz, Juan M.; Ruz, María; ,
Abstract: In recent years, several computer-aided diagnosis (CAD) systems have been proposed for an early identification of dementia. Although these approaches have mostly used the transformation of data into a different feature space, more precise information can be gained from a Searchlight strategy. The current study presents a data fusion classification system that employs magnetic resonance imaging (MRI) and neuropsychological tests to distinguish between Mild-Cognitive Impairment (MCI) patients that convert to Alzheimer's disease (AD) and those that remain stable. Specifically, this method uses a nested cross-validation procedure to compute the optimum contribution of each data modality in the final decision. The model employs Support-Vector Machine (SVM) classifiers for both data modalities and is combined with Searchlight when applied to neuroimaging. We compared the performance of our system with an alternative based on Principal Component Analysis (PCA) for dimensionality reduction. Results show that Searchlight outperformed PCA both for uni/multimodal classification, obtaining a maximum accuracy of 80.9% when combining data from six and twelve months before patients converted to AD. Moreover, Searchlight allowed the identification of the most informative regions at different stages of the longitudinal study, which can be crucial for a better understanding of the development of AD. Additionally, results do not depend on the parcellations provided by a specific brain atlas, which manifests the robustness and the spatial precision of the method proposed. Highlights: The goal of this study is to provide a method for an early detection of Alzheimer's. We combine MR images and psychological tests to study the development of dementia. The contribution of each modality to the decision of the classifier is computed. Searchlight identifies the brain regions that are first affected by Alzheimer's. Our method maximizes classification accuracy while preserving spatial information.